Evaluasi Keberhasilan Penanganan Scale Problem Dengan Metode Acidizing di Sumur “Jose-1” Pada Lapangan “Ma-Mandar” Untuk Meningkatkan Laju Alir Produksi - Aldi, Muhammad; Afifah, Rohima Sera; Firdaus, Firdaus; Battu, Desianto Payung; Laby, Dharma Arung; Mustagina, Amanda (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
Productivity or commonly called productivity index (PI) in a well will decrease. Marked by a decrease in reservoir pressure (Pr), well flowing pressure (Pwf) and rate (Q) in the "Jose-1" well also decreased due to deposits (Scale) formed in the production zone, thus inhibiting Pr, Pwf and Q. Therefore, the solution that can be done to overcome this problem is well stimulation. The purpose of well stimulation in the "Jose-1" well is to overcome the deposits (Scale) formed so that Q increases. The deposits (Scale) formed can be identified by formation water parameters using several methods, one of which is the Stiff and Davis method with the Scaling Index (SI) parameter obtained. The stimulation method used is the matrix acidizing method, the success parameters of the matrix acidizing method can be seen from the Inflow Performance Relationship (IPR) parameters before and after as well as the PI before and after. This Final Assignment writing is done using manual calculations via excel. Based on the results of the analysis carried out, the "Jose-1" well experienced a decrease in pressure and production flow rate caused by CaCO3 deposits (Scale), proven by the SI value parameters using the Stiff and Davis method where SI> 0 (Tends to precipitate or precipitate CaCO3) which is 1.13 and a skin value of 12.5. After acid injection was carried out on the well, the oil rate (Qo) from 90 bopd increased to 144,539 bopd.